Cooperative Action of SLR1 and SLR2 Is Required for Lateral Root-Specific Cell Elongation in Maize - Hochholdinger, Frank (American Society of Plant Physiologists, 2001)
Lateral roots play an important role in water and nutrient uptake largely by increasing the root surface area. In an effort to characterize lateral root development in maize (Zea mays), we have isolated from Mutator (Mu) transposon stocks and characterized two nonallelic monogenic recessive mutants: slr1 and slr2 (short lateral roots1 and 2), which display short lateral roots as a result of impaired root cell elongation. The defects in both mutants act specifically during early postembryonic root development, affecting only the lateral roots emerging from the embryonic primary and seminal roots but not from the postembryonic nodal roots. These mutations have no major influence on the aboveground performance of the affected plants. The double mutant slr1; slr2 displays a strikingly different phenotype than the single mutants. The defect in slr1; slr2 does not only influence lateral root specific cell elongation, but also leads to disarranged cellular patterns in the primary and seminal roots. However, the phase-specific nature of the single mutants is retained in the double mutant, indicating that the two loci cooperate in the wild type to maintain the lateral root specificity during a short time of early root development.